Toward normalization of Japan's security and defence policy - Benjamin Schreer (Stiftung Wissenschaft und Politik (SWP), 2005)
On December 10, 2004, the Japanese government adopted the new National Defense Program Outline (NDPO). Setting out the defense doctrine and the military capabilities required to fulfill it, the NDPO was received by international media as evidence for a substantial reorientation in Japan's security and defense policy. To what extent is this claim justified? What are possible regional and global implications?(SWP Comments / SWP)
Keywords: 320